Contemporary approaches in literary trauma theory - Balaev, Michelle (Palgrave Macmillan, 2014)
"Contemporary Approaches in Literary Trauma Theory showcases some of the leading scholars in literary criticism who take trauma studies in a new direction by broadening the theoretical foundations and future directions of the field through innovative analyses of trauma in literature and culture. Trauma causes a disruption, but the values attached to this experience are influenced by a variety of individual and cultural factors that change over time. Trauma may at times forever silence one, yet trauma can equally at times reorient consciousness in an adaptive fashion that eschews pathology. This collection of essays argues that trauma in literature must be read through a theoretical pluralism that allows for an understanding of trauma's variable representations that include yet move beyond the concept of trauma as pathological and unspeakable"